Best practices for acceptability of GM crops field trials conclusions: Lessons for Africa - Chege, Paul; Njagi, Julia; Komen, John; Ngure, Godfrey; Muriuki, John; Karembu, Margaret (Informa UK Limited, 2024)
The ability to transfer information about the performance, safety, and environmental impacts of a genetically modified (GM) crop from confined field trials (CFTs) conducted in one location to another is increasingly gaining importance in biosafety regulatory assessment and decision-making. The CFT process can be expensive, time-consuming, and logistically challenging. Data transportability can help overcome these challenges by allowing the use of data obtained from CFTs conducted in one country to inform regulatory decision-making in another country. Applicability of transported CFT data would be particularly beneficial to the public sector product developers and small enterprises that develop innovative GM events but cannot afford to replicate redundant CFTs, as well as regulatory authorities seeking to improve the deployment of limited resources. This review investigates case studies where transported CFT data have successfully been applied in biosafety assessment and decision-making, with an outlook of how African countries could benefit from a similar approach.